The Administrative Law of Section 33 of the Charter - Yu, Andy (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2025)
Section 33 of the Canadian Charter of Rights and Freedoms (Charter) can be used to ensure that legislation operates notwithstanding sections 2 or 7 to 15 of the Charter, but can it be used to ensure that administrative decisions made under legislation survive notwithstanding those provisions, and if so, how? This administrative law—as opposed to purely constitutional law—question has become a live one, given increasing use of section 33 and the evolving framework for assessing whether administrative decisions comply with the Charter. Yet this question is underexplored. In this article, I suggest that section 33 can, in principle, be used to ensure that administrative decisions survive notwithstanding the relevant provisions. I then examine whether section 33 can, in fact, be used in this way—and if so, how. Given the evolving framework for assessing whether administrative decisions comply with the Charter, I distinguish between two general approaches to the framework—one based on Charter rights and the other based on Charter values—and explain the effect of using section 33 in the context of administrative decisions on each approach. On the Charter rights approach, using section 33 has effects that are analogous to the effects of using section 33 in the context of legislation; at the least, it prevents a court from quashing the decision. On the Charter values approach, however, using section 33 has no effect, since using section 33 has no effect on Charter values or their enforcement.